IMPLEMENTASI CHATBOT BERBASIS ARTIFICIAL INTELLIGENCE DALAM PEMBELAJARAN MAHARAH KITABAH MAHASISWA - Abd. Salam Cahya Sasmita Jd.; Moh. Supriyadi; Fatmawati Fatmawati (Fakultas Teknik Universitas Negeri Makassar, 2026)
The rapid development of Artificial Intelligence (AI) technology has brought various innovations to the field of education, including the use of chatbots as language learning media. This study aims to describe the implementation of AI-based chatbots in teaching Maharah Kitabah (Arabic writing skills) to university students and to examine students’ perceptions of their use. The research employs a qualitative descriptive approach, with participants drawn from students of the Arabic Language Education program. Data were collected through classroom observations, questionnaires, and limited interviews. The findings indicate that the use of AI-based chatbots assists students in generating ideas, improving sentence structure, and enhancing motivation to write in Arabic. Moreover, chatbots function as flexible and responsive learning companions, although certain limitations were identified, particularly in terms of linguistic accuracy and students’ dependency on technology. This study concludes that AI-based chatbots have the potential to serve as an alternative medium for teaching Maharah Kitabah; however, pedagogical guidance is necessary to ensure their effective and proportional use.